G374(P) Evidence based guideline reduces inappropriate treatment in bronchiolitis – a completed audit cycle. (24th May 2017) - Vasi, V; Diamond, C; Mackle, R; Bourke, T
Abstract : Bronchiolitis is a seasonal viral lower respiratory tract illness common in infancy and a major cause of hospitalisation in this age group. The course is often self-limiting. Mainstay of management is supportive care to maintain oxygenation and hydration. We developed local guidelines for the management of bronchiolitis based on recommendations from NICE and Bronchiolitis of Infancy Discharge Study (BIDS). Key messages being: minimal handling and suctioning, rare pharmacological treatment in selected cases and permissive approach to patients with saturations>90% (BIDS). This guidance was implemented using a robust teaching program for all staff including nurses and junior doctors. We aimed to audit current management of bronchiolitis and compliance with new guideline. We also compared outcomes with practice before implementation of new guideline. Methods: An audit proforma was designed and the new trust guideline – 2015/2016 was used as gold standard. Data was collected using clinical coding, case notes, electronic case records. Data on 30 patients admitted with bronchiolitis between October 2014 to December 2014 was collected. The new guideline was implemented in December 2015. We collected data on infants admitted with bronchiolitis between 1st January and 31st March 2016 in RBHSC. A total of 29 patients were included in this cohurt. Results: Suctioning was reduced from 83% to 34%, so as the use of hypertonic saline nebulisers. There was a slight increase in the use of antibiotics. No change was seen with regards to duration of stay. 1 patient was readmitted in 2016 compared with 5 patients in 2014. Conclusion: Compliance to the new guideline was good and minimal handling and suctioning did not prolong the stay or readmission.